Karakterisasi dan Potensi Pasir Besi Formasi Kabuh Daerah Mlale, Kecamatan Jenar, Kabupaten Sragen, Provinsi Jawa Tengah - Afri Tri Kristanto; Al Hussein Flowers Rizqi (Retii, 2021)
Characterization and potential of sand deposits in the Kabuh Formation at Mlale Region because gray-black sand deposits were found with magnetic properties, interpreted as iron sand. The purpose of this study was to determine the characteristics and potential of iron sand deposits. The research methods used are detailed observations, rock sampling, laboratory activities for petrology and XRF geochemical analysis, studio activities for data interpretation. The geological condition shows 1 – 3 meters gray-black sand deposits with +20 meters layer. The petrological analysis shows the grain size fine – coarse sand, slightly rounded – angular shape, opaque minerals is 66% megascopically and microscopically 23%. Sand deposits are interpreted as alluvial placer deposits from Nglanggran Formation and Kebobutak Formation at the Southern Mountains Zone, as well as the Anggota Banyak Kalibeng Formation and Pucangan Formation from Kendeng Zone. The enrichment factor is from magnetic minerals on source rock and the basin topography, but the destruction factor is not well developed. XRF geochemical analysis showed 4.41% Fe content and 7.71% hematite (Fe2O3) content. This grade can’t be processed and refined as metal mineral. Increasing the value can be better by filtering and separation.